Using a Mobile Phone as a "Wii-like" Controller for Playing Games on a Large Public Display. (17th December 2007) - Vajk, Tamas; Coulton, Paul; Bamford, Will; Edwards, Reuben
Abstract : Undoubtedly the biggest success amongst the recent games console releases has been the launch of the Nintendo Wii. This is arguably due to its most innovative attribute—the wireless controller or "Wiimote." The Wiimote can be used as a versatile game controller, able to detect motion and rotation in three dimensions which allows for very innovative game play. Prior to the Wii, and with much less furor, Nokia launched its 5500 model phone which contains 3D motion sensors. Using the Sensor API library available for the Symbian OS, this sensor data can be used by developers to create interesting new control schemes for mobile games. Whilst 3D motion can be utilized for ondevice games, in this paper we present a novel system that connects these phones to large public game screens via Bluetooth where it becomes a game controller for a multiplayer game. We illustrate the potential of this system through a multiplayer driving game using the Microsoft XNA framework and present preliminary feedback on the user experience from a public trial which highlights that these controls can be both intuitive and fun.